The Impact of tourism in East Africa : a ruinous system - Storch, Anne; Mietzner, Angelika (Tourism and cultural change ;, 2021)
"This book explores the relationship between imperial formations and individual encounters at African tourist sites. It examines how encounters between tourists and hosts tend to be constructed along colonial thought lines and shows that ruination is omnipresent in postcolonial tourist settings. This book is open access under a CC BY ND licence"--